Three generational bearers’ diverging perception on nicknames in Rokan Hulu, Riau - Saputra, Nofathana; Tur, Ajar Pradika Ananta (Universitas Ahmad Dahlan, 2025)
There is an increasing interest and study regarding nicknames in the last decade. Names serve as more than mere symbols and can represent social standing, ethnicity and contribute to social structures. Nicknames often time can reflect a person’s personality, occupation and even ancestry, it also has been given to people for a very long time in many different cultures, while also fostering a sense of closeness and familiarity among individuals. This study is held in purpose of investigating the custom of intergenerational nicknaming custom of Rokan Hulu, Riau and to understand the influence it has regarding the perception of its bearer of three generation of people in Rokan Hulu, Riau. The study utilized a descriptive qualitative research method to explore the significance of nicknames, analyzing literature regarding the topic, and utilizing a Google Form questionnaire to gather data on the date of birth, meanings, and reasons behind these nicknames. The study reveals that Nickname practices in Rokan Hulu, Riau, have various features, including physical, behavioral, habitual, and place features. These nicknames create different perceptions among generations, with older generations accepting them as part of their identity, while millennials stood within a junction between accepting the name or view them as insults, and Gen Z totally view them as mockery or insults.